2011
DOI: 10.1002/tea.20451
|View full text |Cite
|
Sign up to set email alerts
|

Promoting minority success in the sciences: The minority opportunities in research programs at CSULA

Abstract: Given the large continued investment by the federal government in programs that promote academic success and the pursuit of advanced degrees in the sciences among members groups traditionally underrepresented in the sciences, there is a strong need for research which provides rigorous investigations of these programs and their impact on the target population. The current study examines programs funded by the National Institutes of Health Minority Opportunities in Research (MORE) Division Office intended to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…While the literature pointed to academic preparedness as a significant factor contributing to success, it did not show as strongly in our primary research. [8][9][10] Some students felt prepared while others felt that their high school education was lacking in some areas. Many participants were concerned about workload expectations in the post-secondary environment.…”
Section: Academic Preparednessmentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature pointed to academic preparedness as a significant factor contributing to success, it did not show as strongly in our primary research. [8][9][10] Some students felt prepared while others felt that their high school education was lacking in some areas. Many participants were concerned about workload expectations in the post-secondary environment.…”
Section: Academic Preparednessmentioning
confidence: 99%
“…The students' feelings of preparedness did not match with the researchers' experience in the classroom, the students' postsecondary academic results, or the literature. [8][9][10] This could be due to a number of factors, such as, lack of awareness by the students' regarding academic expectations and interviewing many of the students at the beginning of the year before they were academically challenged in post-secondary school. Additionally, some of the participants performed well academically in post-secondary education, therefore, their feelings of preparedness were founded.…”
Section: Academic Preparednessmentioning
confidence: 99%
“…Slovacek, Whittinghill, Flenoury and Wiseman's () study of the programs funded by the National Institute of Health Minority Opportunities in Research and Education (MORE) found that the stipends and fellowships provided to undergraduate students doing research in the health sciences were essential to the students’ persistence in their degree programs and in the field. Financial support was noted as one piece of the success of the program—faculty mentoring and academic preparation were also highlighted as a key parts of the program design.…”
Section: Research On Institutional Approachesmentioning
confidence: 99%
“…Although considered generally successful in attracting and training students in science, technology, engineering, and mathematics (STEM) fields, federally mandated and funded programs targeting minorities have been found less successful in transforming minority participation in STEM into the biomedical pipeline. They have been under review and discussion for several years 1–5. Over recent decades, these programs have done a great deal for many students and greatly assisted them onto the path of becoming a research scientist by enabling them to graduate from college and enter graduate programs at a higher rate 1,5.…”
mentioning
confidence: 99%
“…They have been under review and discussion for several years 1–5. Over recent decades, these programs have done a great deal for many students and greatly assisted them onto the path of becoming a research scientist by enabling them to graduate from college and enter graduate programs at a higher rate 1,5. The sources of dissatisfaction expressed in the 2005 Committee for the Assessment of the National Institutes of Health (NIH) Minority Research Training Programs report3 and others derive from overly ambitious goals to change the ethnic and gender composition of the biomedical workforce and a lack of definite knowledge about the overall impact of any particular program.…”
mentioning
confidence: 99%